A lotus grows in the mud - Hawn, Goldie (G.P. Putnam's Sons, 2005)
With her trademark effervescent humor, Goldie tells us about the lessons she's learned and the wisdom she feels she's been given, in the hope of giving something back. Not a Hollywood "tell-all," this book is a very personal look at moments private and powerful, a trip back through a life well lived by a woman well loved. She takes us on a tour of her go-go dancing years in New York in the sixties, her phenomenal success on TV's Rowan & Martin's Laugh-In, and then on to the world of Hollywood stardom and such memorable films as the Oscar-winning Cactus Flower, Swing Shift, and Private Benjamin. She speaks of her relationship with her family--her partner, Kurt Russell; her children, Kate Hudson, Oliver Hudson, Wyatt Russell, and her stepson, Boston Russell--her growing faith, her curiosity for that which she doesn't yet know, and her unquenchable thirst for knowledge and understanding.